Environmental management : readings and cases - Russo, Michael V. (Los Angeles, California : Sage, 2008)
With 70% of the entries new to this edition, the Second Edition continues to provide unrivalled coverage of current and emerging topics within business and the environment.
Preface PART I The Big Picture -- 1. Beyond Greening: Strategies for a Sustainable World - Stuart L. Hart Thinking Globally and Inclusively About Sustainable Business Practices -- 2. The Business Case for Climate Protection - L. Hunter Lovins Why Businesses Should Proactively Address the Climate Change Challenge -- 3. Scorched Earth: Will Environmental Risks in China Overwhelm Its Opportunities? - Elizabeth Economy and Kenneth Lieberthal The China Factor in the Environmental Equation -- 4. The Triple Bottom Line: Sustainability's Accountants - John Elkington The Imperative for Companies to Perform Well on Multiple Dimensions -- PART II Institutional and International Perspectives -- 5. The Tragedy of the Commons - Garrett Hardin The Classic Discussion of Population and Common Resources -- 6. EPA and the Evolution of Federal Regulation - Paul R. Portney Regulation and Economic Models for Meeting Pollution Reduction Goals -- 7. Discounting the Future: Economics and Ethics - Timothy J. Brennan A Critical Analysis of the Practice of Discounting in Economic Analysis -- 8. Measuring Nations' Environmental Sustainability - Marc A. Levy Quantifying and Ranking National Environmental Performance -- 9. Bridging the Trade-Environment Debate - Daniel C. Esty Capturing the Benefits of Free Trade While Protecting the Environment -- 10. Raising Global Standards: Hazardous Substances and E-Waste Management in the European Union - Henrik Selin and Stacy D. VanDeveer A European Approach to Toxics Regulation -- PART III Managing to be Environmentally Responsive -- 11. Strategy Originates Within the Organization - Andrew W. Hoffman Behavioral and Cultural Dimensions in Environmental Strategy -- 12. Objection-Handling Clinic on Inhibiters to the Next Wave - Bob Willard A Script for Overcoming Organizational Nay-Sayers -- 13. The Next Industrial Revolution - Paul Hawken, Amory Lovins, and L. Hunter Lovins Capitalism that Recognizes and Appreciates Living Systems -- 14. Environmental Product Differentiation: Implications for Corporate Strategy - Forest Reinhardt When Will a Green Product Strategy Pay Off? -- 15. Transparency, Openness, and Accountability: A Imperative - David L. Rainey Appreciating the Need for Broad Access to More Information -- 16. A Primer on the Global Reporting Initiative - Kellie Fox, Beth Littlehales, and Ryan Keenan The Emerging Standard for Company Sustainability Report -- 17. The Eco-Advantage - Inc. Magazine Entrepreneurship, Innovation, and Sustainability Opportunities -- 18. Excerpts from the 2006 Understanding the LOHAS Market Report - The Natural Marketing Institute Appreciating the Characteristics of Green Consumers -- 19. Avoiding Green Marketing Myopia: Ways to Improve Consumer Appeal for Environmentally Preferable Products - Jacquelyn A. Ottman, Edwin R. Stafford, and Cathy L. Hartmann How Win in the Marketplace for Green Products -- 20. How Corporations and Environmental Groups Collaborate - Dennis A. Rondinelli and Ted London How Stakeholders Collaborations Can Improve Environmental Outcomes -- 21. The Fortune at the Bottom of the Pyramid - C. K. Prahalad and Stuart L. Hart The Vast Potential in Serving the World's Poor -- PART IV Technical Perspectives -- 22 A Framework for Management - Brain Nattrass and Mary Altomare Unifying Scientific Principles with Sustainability -- 23. An Introduction to Environmental Accounting as A Business Management Tool - Environmental Protection Agency A Tool Kit for Incorporating the Environment into Accounting Practice -- 24. Note on Life-Cycle Analysis - Susan Svoboda A Methodology for Identifying All Costs Across the Life of Products -- 25. The LCA Impact and Interpretation Stages - Thomas E. Graedel and Braden R. Allenby Quantifying Life Cycle Impacts and Comparing Alternatives -- 26. A World of Abundance - William McDonough and Michael Braungart Viewing Environmental Stewardship as a Design Challenge -- 27. Environmental Management Systems and Eco-Control - Stefan Schaltegger, Roger Burritt, and Holger Petersen Tools for Bringing Environmental Performance to Facility Operations -- PART V Cases -- 28. Pacific Lumber Company - Michael V. Russo -- 29. Oil in the Ecuadorean Rainforest - Christopher A. Cummings, Barbara L. Marcus, R. Edward Freeman, and Jason Lunday -- 30. Hindustan Lever (A): Leaping a Millennium - Aileen Ionescu-Somers, Wolfgang Amann, and Ulrich Steger -- 31. Cost Accounting and Hazardous Waste at Specialty Glass, Inc. - Christopher H. Stinson -- 32. Southern Company: Acid Rain - Forest Reinhardt -- 33. Seventh Generation: Balancing Customer Expectations with Supply Chain Realities - Daniel R.Goldstein and Michael V. Russo -- 34. Environment Product Differentiation by the Hayward Lumber Company - Magali Delmas and Erica Plambeck -- 35. Coastwide Laboratories: Clean and Green - Derek O. Reiber and Michael V. Russo -- 36. Transforming the Global Fishing Industry: The Marine Stewardship Council at Full Sail? - Alexander Nick, Oliver Salzmann, and Ulrich Steger -- 37. Phoenix Organic: Valuing Sustainability while Desiring Growth - Eva Collins, Steve Bowden, and Kate Kearins -- 38. Deja Shoe (A) - Paul Hardy and Stuart L. Hart -- 39. Supply Chain Strategy and Sustainability: The Migros Palm Oil Case - Jens Hamprecht and Daniel Corsten -- 40. Benziger Family Winery - Murray Silverman and Tom Lanphar -- 41. The WEEE Challenge - Panfeng Chen, Priya Narayan, and Luk N. Wassenhove -- 42. Cascades Environmental Strategy in 2006: At the Crossroads - Pierre Batellier and Emmanuel Raufflet -- 43. Procter & Gamble Inc: Disposable and Reusable Diapers-A Life-Cycle Analysis Management Institute for Environment and Business -- 44. Alpha Motors, Ltd.: Integrating Life-Cycle Environmental Concerns Into Product Design - Sandra Rothenberg, Michael Lenox, Benjamin Jordan, and Frank Field III -- About the Editor
Includes bibliographical references and index.
Keywords: ENVIRONMENTAL MANAGEMENT -- CASES